Ambidexterity and Knowledge Strategy in Major Projects: A Framework and Illustrative Case Study. Issue 5 (15th September 2014) - Turner, Neil; Maylor, Harvey; Lee‐Kelley, Liz; Brady, Tim; Kutsch, Elmar; Carver, Stephen
ABSTRACT: We develop a framework to analyze the multi‐level knowledge requirements of complex, major projects in terms of ambidexterity —the ability to exploit (refine existing knowledge) and explore (develop new knowledge). This is an important theme within the wider literature, yet practical operationalization methods for managers and researchers are not evident. We demonstrate the ambidexterity view through an illustrative case study of telecommunications delivery for the London 2012 Olympic Games and show how these concepts can be used to create an effective knowledge strategy. We offer a structure for the analysis of knowledge utilization in projects.